The sexual and reproductive health of young people in Latin America: evidence from WHO case studies La salud sexual y reproductiva de los jóvenes en América Latina: evidencia derivada de estudios de la OMS - Kate Kostrzewa (Instituto Nacional de Salud Pública, 2008)
This original article addresses the sexual and reproductive health needs of young people aged 15 to 24 in Latin America. It introduces five articles from original research projects in three countries: Argentina, Brazil, and Peru. These projects were funded by the World Health Organization. This article explains the importance of studies that address the sexual and reproductive health of young people in developing countries. It provides an overview of sexual and reproductive health issues in Latin America and a discussion these issues in the three study countries. The five articles deal with difficult and challenging issues, including: knowledge of STIs and HIV/AIDS; pregnancy related practices; quality of care; the role of young men in couple formation, pregnancy and adoption of contraceptive practice; and, the role of obstetricians and gynecologists in public policy debate about family planning and abortion. The four articles in this special section help to improve our understanding of the factors that contribute to risky sexual behavior and negative reproductive health outcomes among youth in Latin America. The findings are useful to help inform and improve health care interventions in various contexts. Este artículo original trata de las necesidades de salud sexual y reproductiva de jóvenes entre 15 y 24 años de edad en América Latina. Se presentan cuatro artículos derivados de investigaciones originales en tres países: Argentina, Brasil y Perú. Estos proyectos fueron patrocinados por la Organización Mundial de la Salud. Este artículo elucida la importancia de los estudios que tratan de la salud sexual y reproductiva de jóvenes en países en desarollo. Se ilustra el panorama general en cuestiones de salud sexual y reproductiva en América Latina y una discusión de estas cuestiones en los tres países de donde provienen los estudios. Los cinco artículos discuten cuestiones difíciles y controversiales, como los conocimientos sobre ITS y VIH/SIDA; las prácticas asociadas con el parto; la calidad de cuidados; el papel de los hombres jóvenes en la formación de parejas, el embarazo y el uso de métodos anticonceptivos; así como el papel de los tocólogos y ginecólogos en el debate público sobre planificación familiar y aborto. Los cuatro artículos en esta sección especial promueven un mejor entendimiento de los factores que contribuyen a las conductas sexuales de riesgo y a los resultados negativos en salud reproductiva entre los jóvenes en América Latina. Las conclusiones son útiles para informar y mejorar intervenciones de servicios de salud en contextos varios.